Loss of gene information: Discrepancies between rna sequencing, cdna microarray, and qrt-pcr - Rachinger, Nicole; Fischer, Stefan; Böhme, Ines; Linck-Paulus, Lisa; Kuphal, Silke; Kappelmann-Fenzl, Melanie; Boßerhoff, Anja Katrin (International Journal of Molecular Sciences, 2021)
Molecular analyses of normal and diseased cells give insight into changes in gene expression and help in understanding the background of pathophysiological processes. Years after cDNA microarrays were established in research, RNA sequencing (RNA-seq) became a key method of quan-titatively measuring the transcriptome. In this study, we compared the detection of genes by each of the transcriptome analysis methods: cDNA array, quantitative RT-PCR, and RNA-seq. As expected, we found differences in the gene expression profiles of the aforementioned techniques. Here, we present selected genes that exemplarily demonstrate the observed differences and calculations to reveal that a strong RNA secondary structure, as well as sample preparation, can affect RNA-seq. In summary, this study addresses an important issue with a strong impact on gene expression analysis in general. Therefore, we suggest that these findings need to be considered when dealing with data from transcriptome analyses.
CRIS-Team Scopus Importer:2021-09-10
Keywords: CDNA microarray; Free energy of the RNA secondary structure; QRT-PCR; RNA sequencing; Secondary struc-ture; Transcriptome analysis